Analysis of hydrodynamic journal bearings considering lubricant supply conditions - Claro, José Carlos Pimenta (1993)
A method of analysis of steadily loaded hydrodynamic journal bearings with a single axial groove (either on the load line or at 90o to the load line) or two diametrically opposed axial grooves is described. The method is based on Elrod's cavitation algorithm (which ensures conservation of mass flow in both the full film and the cavitated regions) and is able to accommodate specified lubricant supply conditions, namely groove size and location and supply pressure. Special attention has been given to the determination of flow rate. The equation governing the distribution of pressure around the bearing has been solved numerically using a finite differences approximation and multi-grid techniques to accelerate the convergence of the solution. Performance predictions of the analysis are compared with published experimental data and with experimental measurements obtained in laboratory tests carried out by the authors. The data used cover all grooving arrangements studied.